2016
DOI: 10.1002/dev.21396
|View full text |Cite
|
Sign up to set email alerts
|

Three‐month‐old infants’ sensitivity to horizontal information within faces

Abstract: Horizontal information is crucial to face processing in adults. Yet the ontogeny of this preferential type of processing remains unknown. To clarify this issue, we tested 3-month-old infants' sensitivity to horizontal information within faces. Specifically, infants were exposed to the simultaneous presentation of a face and a car presented in upright or inverted orientation while their looking behavior was recorded. Face and car images were either broadband (UNF) or filtered to only reveal horizontal (H), vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…It is therefore optimal for the human visual system to make preferential use of this information when performing identity-related tasks, and unsurprising that efficient use of this information predicts face identification performance, while less efficient use of this information predicts the magnitude of the deficit resulting from picture-plane inversion (Pachai et al, 2013). We show that the increased expertise resulting from personal familiarity improves this horizontal selectivity, which has been observed in infants as young as 3 months of age (de Heering et al, 2016).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It is therefore optimal for the human visual system to make preferential use of this information when performing identity-related tasks, and unsurprising that efficient use of this information predicts face identification performance, while less efficient use of this information predicts the magnitude of the deficit resulting from picture-plane inversion (Pachai et al, 2013). We show that the increased expertise resulting from personal familiarity improves this horizontal selectivity, which has been observed in infants as young as 3 months of age (de Heering et al, 2016).…”
Section: Discussionmentioning
confidence: 51%
“…In recent years, several studies have revealed the importance of structure conveyed by horizontally oriented spatial frequency components for face processing (Dakin & Watt, 2009;Goffaux & Dakin, 2010;Goffaux & Greenwood, 2016;Pachai et al, 2013). This information plays a crucial role for face-related tasks throughout the lifespan, with preferential processing of horizontal structure demonstrated as early as 3 months of age (de Heering et al, 2016), and through older age (Goffaux, Poncin, & Schiltz, 2015;Pachai, Corrow, Bennett, Barton, & Sekuler, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent developmental studies indicate that the maturation of face-specialized processing over the lifespan (indexed by an increase in FIE size) depends on the extensive experience humans acquire at encoding the horizontal information conveyed by upright faces 20 (see also refs 21 and 22 ). The horizontal advantage is likely to arise because this orientation range gives access to the most stable and informative facial cues to identity, namely the vertical arrangement of the horizontally-oriented bands containing the eyes, brows, and mouth 2 23 24 25 26 .…”
mentioning
confidence: 99%
“…Consistent evidence indicates that the processing of face identity is tuned to horizontally oriented input; it declines progressively as visual input is oriented away from horizontal, and reaches its minimum when based on vertically-oriented cues. This horizontal tuning is already present in infants and strengthens until adulthood [10][11][12]. We further showed that horizontally-filtered face images trigger the largest response in the Fusiform Face Area (FFA), a high-level visual region responding preferentially to faces ( [13]; see [14,15] for EEG evidence of a horizontal dependence of face-specialized neural responses at a latency corresponding to high-level processing stages).…”
Section: Introductionmentioning
confidence: 66%